Nigerian Corruption, Good Governance, And Effective Leadership: Overcoming The Interface - Ajiteru,S.A.R; Sulaiman T.H; Abalaka, J.N (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
The purpose of the study was to assess how strong leadership affected Nigerian organizations' performance. A questionnaire and structured interview questions were used for the evaluation, which was intended to ascertain the effect of good leadership on the organization's performance; evaluating the impact of the relationship between effective leadership and organizational performance in fostering the maximization of the organization's objectives; determining whether there are any potential means of improving organizational performance; and analyzing whether there are three leadership barriers that impede organizational performance. The study looks at the chances of strong leadership in maintaining Nigeria's good governance. This acknowledges how the idea of